2010
DOI: 10.1007/s00296-010-1479-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD28 serum levels are not associated with specific clinical activity in systemic lupus erythematosus

Abstract: CD28 is one of the main activator receptors involved in systemic lupus erythematosus (SLE) pathogenesis, and its expression and serum levels are significantly higher in patients with SLE and other autoimmune diseases than in healthy controls (HC). However, it is unknown whether this increase is associated with specific organ damage. Therefore, our objective was to measure the CD28 levels in serum from SLE and HC groups to confirm the CD28 serum levels increase, as reported previously, and to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The role of CD28, a costimulatory molecule expressed on the surface of T-cells, has been an issue in evaluating disease activity in SLE. [18][19][20] This study showed a significant decrease in the expression of the CD28 surface marker among patients diagnosed with SLE, particularly in those with active SLE, when compared to healthy participants. Based on previous observations in patients with SLE have revealed a reduction in CD28 surface marker expression on T-cells, which has been linked to both disease activity and severity.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The role of CD28, a costimulatory molecule expressed on the surface of T-cells, has been an issue in evaluating disease activity in SLE. [18][19][20] This study showed a significant decrease in the expression of the CD28 surface marker among patients diagnosed with SLE, particularly in those with active SLE, when compared to healthy participants. Based on previous observations in patients with SLE have revealed a reduction in CD28 surface marker expression on T-cells, which has been linked to both disease activity and severity.…”
Section: Discussionmentioning
confidence: 60%
“…11,12 Despite that, few studies had been demonstrated the performance of this marker for the monitoring of SLE disease activity. 19 The correlation between the CD28 surface marker and the CD28 soluble marker is complex. Under certain conditions, CD28 can be cleaved from the T-cell surface, releasing sCD28 into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from different studies have included decreased percentages of CD4+CD28+ and CD8+CD28+ T cells among patients with SLE (Alvarado), no significant difference in CD4+CD28+ T‐cell proportion between groups (Bijl), and no difference in overall CD28+ T‐cell proportion but increased proportion of CD8+CD28+ T cells among patients with SLE (Tulunay) . Additionally, increased CD28 expression may not correlate directly with clinical activity in patients with SLE . However, responder T cells from patients with SLE show a loss of CTLA‐4–mediated inhibition of CD3/CD28 costimulation .…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Additionally, increased CD28 expression may not correlate directly with clinical activity in patients with SLE. 23 However, responder T cells from patients with SLE show a loss of CTLA-4-mediated inhibition of CD3/CD28 costimulation. 24 Taken together, these data are indicative of the central role played by the CD28/CTLA-4-CD80/86 costimulatory pathway in the defective immune response observed in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…16 Peningkatan kadar serum CD28 mungkin merupakan hasil dari ekspresi berlebih gen CD28, yang dapat dikaitkan dengan penurunan sel limfosit T CD28+, hiporesponsif sel limfosit T dan gangguan kekebalan yang terjadi pada pasien LES. 17 Molekul sCD28 ini dapat diproduksi dengan pelepasan bentuk membran, atau dari splicing mRNA alternatif, tetapi hasil analisis PCR terbaru menunjukkan bahwa peningkatan sCD28 dalam sirkulasi darah lebih mungkin disebabkan karena pelepasan dari bentuk membran. 16 Dari penjelasan di atas, dapat diketahui bahwa molekul kostimulatori terlarut sCD28 dapat dikembangkan sebagai biomarker prediktif yang menjanjikan dari sistem penuaan imun di masa yang akan datang.…”
Section: Perbedaan Kadar Scd28 Pada Individu Muda Les Dan Lansiaunclassified